2-Hydroxy-3-iodo-4-n-butoxy-5-bromopropiophenone Oxime as An Analytical Reagent for Copper(II) - Dave, J.A.; Shah, S.S. (Asian Journal of Chemistry, 2010)
2-Hydroxy-3-iodo-4-n-butoxy-5-bromopropiophenone oxime has been used for the spectrophotometric determination for Cu(II) at pH range of 6 to 9 in chloroform medium. Jobs' method for continuous variation, Yoe and Jones' mole ratio method, the slope ratio method show metal ligand ratio in complex to be 1:2. The stability constant of the complex is found to be 6.29 × 108. The green coloured complex obeys Beer's law in the concentration range 20.96 to 222.39 ppm for Cu(II) ion, while the optimum concentration range from Ringbom plot is found to be 20.96 to 177.82 ppm. The photo-metric sensitivity and molar absorptivity at the 640 nm are found to be 0.031 μg/cm2 and 202 l mol-1 cm-1, respectively. The standard free energy of formation of complex is -1.219 kcal/mol at 30 ºC. The complex is stable for 2 weeks. The reagent has also been found to give quite satisfactory results for Cu(II) present in alloy like brass and bronze.